Effects of Fungi-Mediated Solid-State Fermentation on Phenolic Contents and Antioxidant Activity of Brown and White Teff (Eragrostis tef (Zucc.) Trotter) Grains - Yoseph Asmelash Gebru; Desta Berhe Sbhatu (Journal of Food Quality)
Teff (Eragrostis tef (Zucc.) Trotter) is a tropical cereal used in preparing a staple food in Ethiopia and Eritrea called injera. Phenolic compounds are available in soluble and bound forms in cereals like teff. Therefore, their bioaccessibility depends on their release from the food matrix. Different food processing methods including fermentation have been applied since ancient times to aid bioaccessibility and improve the properties of food products. This study aimed at investigating changes in phenolic profiles and antioxidant activities of white and brown teff grains during mushroom-mediated solid-state fermentation. Fermentation with mushroom considerably increased total phenol contents of the soluble phenol fraction with Ganoderma lucidum showing relatively higher increase than Pleurotus ostreatus. Bound fraction of teff phenol did not show noticeable changes after fermentation with the two mushroom strains. Such changes are suggested to be attributed to activities of fungal enzymes such as amylases, xylanases, and proteases that induce structural breakdown of grain components including cell walls leading to the liberation or synthesis of a variety of phenolic compounds. On the other hand, total flavonoid content of teff significantly decreased after fermentation by both strains. This is also believed to be caused by the action of fungal polyphenol oxidases that catalyze the oxidation of a variety of phenolic compounds including flavonoids to o-quinones.